EFEKTIVITAS MODEL PBL DALAM MENINGKATKAN KEPERCAYAAN DIRI DAN HASIL BELAJAR DI SMA NEGERI 4 PONTIANAK - Lubis, Dian Fitriani; Mashudi, Mashudi; Khosmas, Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe learning model leads to a particular learning approach including goals, syntax, environment and management system. The learning model is closely related to students learning style and teacher teaching style. Teacher work in teaching students is a very important part of achieving the success of the planned learning goals. Therefore, the choice of various methods, strategies, techniques and learning models is the main thing. The purpose of this study is to analyze the effectiveness of learning problem-based learning (PBL) model in improving self-esteem and learning outcomes of IIS class students on economics subjects at Pontianak High School 4. The research method that will be used in this study is experimental design with the form of experimental design yours sincerely. The data sources in this study are the IIS X classes and the data are the answer students pretest and posttest and self-confidence questionnaires in experimental classes and control classes. The results show that the average implementation of learning models in the excellent category of 96% at meetings 1 and 100% at meetings 2-4, problem-based learning learning models (PBLs) effectively boost student self-esteem evidenced by the result of hypothesis test obtained asymp value. sig. (2-tailed) is 0,000 <0,05 and the problem-based learning-based learning model (PBL) is effective in improving the learning outcomes evidenced by the results of the hypothesis test which has a significant value of 0,000 smaller than the significance value of 0.05. Keywords: Problem Based Learning, Self Confidence, and Study Result.